Translation and linguistic validation of the implementation leadership scale in Chinese nursing context. (21st April 2019) - Hu, Jiale; Gifford, Wendy; Ruan, Hong; Harrison, Denise; Li, Qingge; Ehrhart, Mark G.; Aarons, Gregory A.
Abstract: Aim: To translate the Implementation Leadership Scale (ILS) into Chinese and evaluate how Chinese nursing staff and leaders understood and responded to the Chinese ILS. Background: Leadership is a critical factor for implementing evidence‐based practice. The ILS is a valid and reliable instrument to understand leadership for evidence‐based practice; however, this scale or the other similar instrument does not exist in Chinese. Methods: We followed the translation and cross‐cultural validation guideline developed by Sousa and Rojjanasrirat. Translation included two forward and blind backward translations, and their comparisons. Two rounds of cognitive interview were used to evaluate the linguistic validity. Results: The translation process took 12 months. In the forward and backward translations, 24 translation issues were identified, of which semantic equivalence issues were most frequent. Ten nurses participated in each round of cognitive interviews and 33 linguistic issues were found. The final Chinese ILS had seven significant adaptations to the original instrument. Conclusion: This study provided a deep understanding of using the ILS in the local context and laid the foundation for future psychometric statistical testing. Implications for nursing management: Implementation leadership scale could support organisational leadership development programmes and strategies to facilitate and support EBP implementation and sustainability.